Determination of key soil characteristic parameters using angle of repose and direct shear stress test - Yang, Qizhi; Shi, Lei; Shi, Aiping; He, Mingsheng; Zhao, Xiaoqi; Zhang, Li; Addy, Min (International Journal of Agricultural and Biological Engineering, 2023)
Discrete element modelling (DEM) is a numerical method for examining the dynamic behavior of granular media. In order to build an accurate simulation model and provide more comprehensive soil characteristic parameters for the design and optimization of various soil contact machinery, in this paper, the discrete element simulation method (EDEM) combined with experimental approach is used to investigate the soil contact characteristic parameters in East Asia. In this study, Hertze-Mindlin (no slip) was used as a particle contact model by taking particle contact parameters and soil JKR (Johnson-Kendall-Roberts) surface energy as determinants, and repose angle, internal friction angle, and cohesive force as evaluation indexes. The method of Plackett-Burman, Stepest ascent, and Box-Behnken were used to gradually reduce the range of parameters needed for simulation until the most accurate value was determined. The results show that the restitution coefficient, static friction coefficient, and rolling friction coefficient between soil particles have significant effects on the DEM model, and their value of them are 0.596, 0.725, and 0.16, respectively. Based on these parameters used for the repose angle test and direct shear stress test, the value of repose angle is 31.97°, the internal friction angle is 27.61°, and the cohesive force is 33.06 kPa. The relative errors with the actual measured values are 9.54%, 1.87%, and 2.31%, respectively. In order to further test whether the simulation parameters of soil obtained by repose angle test and direct shear stress test are consistent with the real soil, comparison test between field test and discrete element simulation was used. The results show that the error in height of ridge between the simulated soil and the actual soil is 4.06%, which is within the acceptable range. It also indicates that the calibrated and optimized soil simulation model can accurately represent the real soil. The research provides theoretical basis and technical support for the study of soil contact parts by using the discrete element method, combined with repose angle test and direct shear stress test.Keywords: soil, characteristic parameters, calibration, repose angle, direct shear stress, discrete elementDOI: 10.25165/j.ijabe.20231603.6293Citation: Yang Q Z, Shi L, Shi A P, He M S, Zhao X Q, Zhang L, et al. Determination of key soil characteristic parameters using angle of repose and direct shear stress test. Int J Agric & Biol Eng, 2023; 16(3): 143–150.